Obstacle Analysis And Community Medicine Interprofessional Communication Solutions In Medical And Dental Students - Nina Anggraeni Noviasari; Rifka Widianingrum (Sean Institute, 2023)
Poor communication between doctors, patients and between health professionals, has a negative impact. The patient becomes disobedient to the doctor's intervention, the doctor becomes the target of violence due to the patient's ignorance. The World Health Organization (WHO) initiated Interprofessional Education (IPE) learning at the undergraduate level to improve communication and collaboration of health workers to improve patient health outcomes. This study aimed to analyze the barriers and solutions to community medicine interprofessional communication among medical and dental students. This study uses a qualitative method with a case study design. Observational data collection and focus group discussion (FGD). Students were divided into 16 groups, each consisting of 9 medical students and three dentistry students. Observation of IPE activities on collaborative practices in community residents in Sendangmulyo with five meetings for each group. FGD activities were carried out after collaborative approach with student representatives from each group. The results showed that the obstacles that occurred included: differences in competence and knowledge, lack of cooperation, lack of confidence, signal interference, differences in medical terms, miscommunication, and lack of response. Solutions: collaboration and complementarity, holding offline meetings, building closeness, gathering ideas, respecting each other's opinions, more accurate information, being open and trusting each other, being active listeners, giving others opportunities to express opinions, and using language that is easy to understand, repeating the explanation given